2015
DOI: 10.1039/c5nj00568j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the “bent sandwich-like” divalent lanthanide hydro-tris(pyrazolyl)borates Ln(TpiPr2)2 (Ln = Sm, Eu, Tm, Yb)

Abstract: Synthesis, luminescence and reactivity of the lanthanide(ii) “bent sandwich-like” hydro-tris(pyrazolyl)borate complexes Ln(TpiPr2)2 (Ln = Sm, Eu, Tm, Yb) have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…Lanthanide-based coordination compounds that contain aromatic ligandso ften showe fficient 4f nÀ1 5d 1 !4f n luminescence at low energies (green to red wavelengths). [33][34][35] For the title compound, [{(Cp tBu 2 ) 2 Ce(m-Cl)} 2 ], we want to investigate the opticalp roperties of another efficient photoluminescento rganolanthanidec ompound. Moreover,w ea lso want to illustrate how photoluminescence spectroscopy readily gives insights into the oxidation states of lanthanide atoms in such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-based coordination compounds that contain aromatic ligandso ften showe fficient 4f nÀ1 5d 1 !4f n luminescence at low energies (green to red wavelengths). [33][34][35] For the title compound, [{(Cp tBu 2 ) 2 Ce(m-Cl)} 2 ], we want to investigate the opticalp roperties of another efficient photoluminescento rganolanthanidec ompound. Moreover,w ea lso want to illustrate how photoluminescence spectroscopy readily gives insights into the oxidation states of lanthanide atoms in such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, these investigations have been successfully extended to the even larger hydrotris(3,5diisopropylpyrazolyl)borate ligand (Tp iPr2 ) (Kitajima et al, 1992). Homoleptic complexes of this ligand could be isolated with the 'classical' divalent lanthanides samarium, europium, thulium and ytterbium (Momin et al, 2014;Kü hling et al, 2015). Rather surprisingly, crystal structure determinations revealed a 'bent sandwich'-like molecular structure like Ln(C 5 Me 5 ) 2 ( Fig.…”
Section: Figurementioning
confidence: 99%
“…Computational studies indicated that steric repulsion between the isopropyl groups forces the Tp iPr2 ligands apart and permits the formation of unusual interligand C-HÁ Á ÁN hydrogen-bonding interactions that help to stabilize the structure (Momin et al, 2014). The recently reported neon-yellow divalent europium complex Eu(Tp iPr2 ) 2 also stands out due to its bright-yellow photoluminescence, which has been investigated in great detail (Kü hling et al, 2015;Suta et al, 2017). Eu(Tp iPr2 ) 2 was easily prepared in 83% yield by treatment of the bis-THF adduct of europium(II) diiodide, EuI 2 (THF) 2 , with 2 equiv.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in samarium complexes having polypyrazolylborate ligands (Onishi et al, 1998(Onishi et al, , 2004. In connection with interesting reduction reactions of divalent lanthanides complexes, five divalent hydridotris(pyrazolyl)borate complexes of samarium have been structurally characterized, namely [Sm(Tp tBu;MetBu,Me ) 2 ] [Tp tBu,Me is tris(3-tert-butyl-5-methylpyrazol-1-yl)borate] (Zhang et al, 1995), [Sm(Tp Me 2 ) 2 ] [Tp Me 2 is tris(3,5-dimethylpyrazol-1-yl)-borate], [Sm(Tp Me 2 ;4-Et ) 2 ] [Tp Me 2 ;4-Et is tris(4-ethyl-3,5-dimethylpyrazol-1-yl)borate] and [Sm(Tp Ph ) 2 ] [Tp Ph is tris(3phenylpyrazol-1-yl)borate] (Hillier et al, 2001), and [Sm-(Tp iPr 2 ) 2 ] [Tp iPr 2 is tris(3,5-diisopropylpyrazol-1-yl)borate] (Momin et al, 2014;Kuhling et al, 2015) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%